Quantitative Ultrasound Texture Analysis for Differentiating Preterm From Term Fetal Lungs. (24th March 2017) - Ghorayeb, Sleiman R.; Bracero, Luis A.; Blitz, Matthew J.; Rahman, Zara; Lesser, Martin L.
Abstract : Objectives: To differentiate preterm (<37 weeks' gestation) from term (≥37 weeks' gestation) fetal lungs by using quantitative texture analysis of ultrasound images. Methods: This study retrospectively evaluated singleton gestations with valid dating at 20 weeks' gestational age (GA) or later between January 2015 and December 2015. Images were obtained from Voluson E8 ultrasound systems (GE Healthcare, Milwaukee, WI). A region of interest was selected in each fetal lung image at the level of the 4 heart chambers from an area that appeared most representative of the overall lung tissue and had the least shadow. Ultrasonic tissue heterogeneity (heterogeneity index) based on dynamic range calculation was determined for all lung images. This quantification was performed with a custom‐made software program that used a dithering technique based on the Floyd‐Steinberg algorithm, in which the pixels are transformed into a binary map. Regression analysis was used to determine the correlation and functional association between the heterogeneity index and GA. A receiver operating characteristic curve was used to identify the optimal heterogeneity index cutoff point for differentiating preterm from term fetal lungs. Results: A total of 425 fetal lung ultrasound images (313 preterm and 112 term) were analyzed. Quantitative texture analysis predicted GA with sensitivity and specificity of 87.9% and 92.0%, respectively, based on the optimal receiver operating characteristic cutoff point. Conclusions: Quantitative ultrasound texture analysis of fetal lung tissue can differentiate preterm fetal lungs from term fetal lungs. Our data suggest that decreased fetal lung heterogeneity on ultrasound imaging is associated with preterm fetuses.